ANALISIS PROFIT MARGIN UNTUK MENINGKATKAN NILAI TAMBAH PENDAPATAN ANTAR PENGRAJIN PENGASAPAN IKAN MANYUNG, IKAN TONGKOL DAN IKAN PARI DI BANDARHARJO SEMARANG - Nanang Yusroni (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
This fumigation of fish is one of the businesses that have constraints in terms of business management, which is where the management is not using good business management, or in the other word, traditional fisheries, namely: ways and tools used were simple and there is no accounting / recording of business activity.The observation showed that the fish fumigation business in Kelurahan Bandarharjo, Kecamatan Semarang Utara using traditional technology with simple process and way. The amount of labour needed depends on the magnitute scale of production. Highest production costs are Manyung fish species and the price is more expensive than Tongkol fish and Pari fish. Price and production value is determined by the type of fish that became the raw material, price per piece of fumigated fish and the number of pieces, and the other production.Keywords: Social aspect, Economic aspect, Player of fumigated fish, Cost of production